DOI: 10.33915/etd.1799
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture-related stress on rainbow trout (Oncorhynchus mykiss) and Arctic char (Salvelinus alpinus)

Abstract: Aquaculture-related Stress on Rainbow Trout (Oncorhynchus mykiss) and Arctic Char (Salvelinus alpinus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In the companion study, Nelson (2003) reported that, during the 5.5‐h transport, the plasma cortisol of Arctic char subjected to AQUI‐S, CO 2 and water transport treatments recovered to resting, pretransport levels. Nelson (2003) concluded that CO 2 and ice‐slurry transport treatments were not ideal for reducing stress response. In percussion‐stunned fish, stress caused by CO 2 transport did not affect the muscle pH at harvest in a comparison of this treatment with control and water transport treatments.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the companion study, Nelson (2003) reported that, during the 5.5‐h transport, the plasma cortisol of Arctic char subjected to AQUI‐S, CO 2 and water transport treatments recovered to resting, pretransport levels. Nelson (2003) concluded that CO 2 and ice‐slurry transport treatments were not ideal for reducing stress response. In percussion‐stunned fish, stress caused by CO 2 transport did not affect the muscle pH at harvest in a comparison of this treatment with control and water transport treatments.…”
Section: Resultsmentioning
confidence: 96%
“…During each simulated transport, five fish were removed from each tote every 1.5 h for the analyses of physiological responses to the transport treatments. The physiological responses have been reported elsewhere (Nelson 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The high amount of monounsaturated fatty acids (i.e., 18:1n-9 in rapeseed oil) and saturated fatty acids (i.e., 16:0 in palm oil) makes them suitable as these fatty acids have been reported to be preferred for energy production in fish (Henderson & Sargent, 1985;Kiessling & Kiessling, 1993). In addition, moderate levels of 18:3n-3 are present in rapeseed oil, suggesting a great potential for endogenous conversion to EPA and DHA (Pettersson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The high amount of monounsaturated fatty acids (i.e., 18:1n‐9 in rapeseed oil) and saturated fatty acids (i.e., 16:0 in palm oil) makes them suitable as these fatty acids have been reported to be preferred for energy production in fish (Henderson & Sargent, ; Kiessling & Kiessling, ). In addition, moderate levels of 18:3n‐3 are present in rapeseed oil, suggesting a great potential for endogenous conversion to EPA and DHA (Pettersson, ). Canola oil, a rapeseed oil with low erucic acid and low glucosinolate, is a potential alternative for fish oil in aquafeed, due to its suitable FA profile, abundance, low price and many other advantages (Canola Council of Canada ; Turchini et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation